Dinamika Kelompok dalam Tinjauan Teori Keterkejutan Budaya William Ogburn - Andra Eka Putra (Pusat Pembinaan Jabatan Fungsional Bidang Pengembangan Kompetensi Pegawai ASN, 2020)
A training generally begins with group dynamics which the philosophical basis is an effort toaccelerate the stages forming, stroming, norming, performing (The Tuckman Stages of TeamDevelopment ) through the intervention of games that usually have trait of antics. However, notinfrequently, the opposite trait is actually owned by trainees with introverted personality types which Hans Eysenck called shy, unfriendly and serious. This study then aims to see what impact will result when these two opposing traits are viewed from the perspective of William Ogburn’s Culture Shock theory. The method that been used is library research where the findings indicate that trainees with introverted personality will potentially be left behind from extroverted trainees in following the rhythm of dynamics group training so that the performing stage marked by flexible collaboration is essentially difficult to realize or even though it appears to be a collaboration, the collaboration is merely a formality.